Pemenuhan Hak-Hak Anak Pasca Perceraian - Feni Sagita Indah; Kairuddin Karim; Lia Trizza Firgita Adhilia (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to determine the application of law to the fulfillment of post-divorce children's rights based on Decision Number 147/Pdt.G/2022/PA Pare and to determine legal considerations by judges regarding the fulfillment of post-divorce children's rights based on Decision Number 147/Pdt. G/2022/PA Pare. The type of research used in this research is normative legal research. The approach used in this paper is the statutory approach and the case approach. The results of the research show that the judge has applied the law that has been in force. Whether it's Law Number 1 of 1974 Concerning Marriage and the Compilation of Islamic Law. Because with these references it has an impact or implications for the defendant so that the decision can be carried out, not even ignoring it. that the legal considerations of the judge as described are appropriate and in accordance with the facts obtained at the trial including in the evidence as the implementation of Article 164 HIR regarding evidence in the civil sphere. Whereas in parenting the child is still in the care of the mother because the child is still underage, even so, the father or the defendant can still meet his child so that this is in line with or in accordance with the intent and purpose of Law number 1 of 1974 concerning Marriage and Compilation of Islamic Law (KHI).